Engineered Customizable Microvessels for Progressive Vascularization in Large Regenerative Implants (Adv. Healthcare Mater. 4/2022). Issue 4 (16th February 2022) - Li, Cuidi; Han, Xiaoyu; Ma, Zhenjiang; Jie, Tianyang; Wang, Jinwu; Deng, Lianfu; Cui, Wenguo
Abstract : Injectable Implants In article number 2101836 by Wenguo Cui and co‐workers, an endothelial cells‐laden bioink is uniformly patterned into engineered customizable microvessels with adjustable length via combining a celluar coaxial microfluidic technology and a microsurgery post‐dissection treatment. The customizable microvessels display excellent injectability and outstanding sprouting angiogenesis potential, and thus can be easily introduced into a variety of soft/hard regenerative scaffolds for controllable vascularization promotion.